Effects of metformin supplementation in high-carbohydrate diets on growth performance, glucose metabolism, intestinal flora, and PI3K/AKT signaling pathway of hybrid grouper (Epinephelus fuscoguttatus♀×Epinephelus lanceolatu♂) - Jiasheng Wen; Qintong Yu; Ling Pan; Hongyu Liu; Beiping Tan; Xiaohui Dong; Shuyan Chi; Qihui Yang; Shuang Zhang (Aquaculture Reports)
Metformin, or 1,1-dimethylbiguanide, is a hypoglycemic drug that lowers blood glucose by reducing glycogen synthesis and increasing glucose uptake in peripheral tissues. Six diets with iso-nitrogenous and iso-lipid compositions were prepared, including a positive control (20 % carbohydrate, PC) and a negative control (30 % carbohydrate, T0). The experimental diets contained 0.2 % (T2), 0.4 % (T4), 0.6 % (T6), and 0.8 % (T8) metformin based on the negative control diet. A total of 540 hybrid groupers, with consistent size and health conditions, were randomly assigned to six groups. Each group contained 30 fish, with three replicates per group, and they were fed for eight weeks. The high-carbohydrate diet reduced weight gain, digestive enzyme activities and specific growth rates (P>0.05), while significantly increasing hepatosomatic indices (P<0.05). Metformin supplementation reduced both hepatosomatic and viscerosomatic indices (P<0.05). The high-carbohydrate diet led to increased levels of glucose, triglycerides, low-density lipoprotein, hepatic fructose 1,6-bisphosphatase, and glucose-6-phosphatase in the serum (P<0.05). In contrast, metformin supplementation significantly lowered glucose, insulin, triglycerides, and low-density lipoprotein levels (P<0.05), while enhancing the activities of hepatic glucokinase, phosphofructokinase-1, and pyruvate kinase (P<0.05). It significantly reduced the activities of PEPCK and G6Pase and downregulated the expression of ir, pi3k, pdk, ampkα1, and gs in fish on high-carbohydrate diets, while metformin supplementation upregulated the expression of ir, pi3k, pdk, ampkα1, and gs genes compared to the T0 group (P<0.05). In terms of microbiota, a high-carbohydrate diet increased pathogenic bacteria like Proteobacteria and Photobacterium, while metformin boosted beneficial bacteria such as Firmicutes and Brevibacillus. Overall, the high-carbohydrate diet impaired growth and insulin sensitivity, while metformin improved glucose metabolism, promoted beneficial bacteria, and supported intestinal health.